ANALISIS PENERAPAN COSO FRAMEWORK TERHADAP KEBERHASILAN SISTEM PENGENDALIAN INTERNAL SIKLUS PRODUKSI PT. YONGJIN JAVASUKA GARMENT FACTORY II - Safitri, Intan Kusdiana; Setiawan, Ade Budi; Hutomo, Yoyok Priyo (Jurnal Akuntansi Kompetif, 2025)
This study aims to analyze the effect of implementing the COSO Framework on the success of the internal control system in the production cycle at PT. Yongjin Javasuka Garment Factory II. The research method used is quantitative with a descriptive approach. Data were collected by distributing questionnaires to 100 respondents of production employees. The results of the analysis show that partially and simultaneously, the five COSO components, namely the control environment, risk assessment, control activities, information and communication, and supervision have a significant effect on the success of the internal control system in the production cycle. The R square value of 0.853 indicates that 85.3% of the variation in the success of the internal control system is explained by these variables. The implications of this study emphasize the importance of implementing the COSO framework as a whole to improve efficiency, effectiveness, and compliance in the production process. Keywords: COSO Framework, Internal Control System, Production Cycle, Effectiveness, Efficiency